Knowledge Regarding Diabetes Mellitus among Rural People in a Selected Area of Bangladesh - Imtiaz, Khondker Saif; Chowdhury, Mahmuda; Nazneen, Humaira; Begum, Nasreen; Tamanna, Nushrat; Alam, Fardous; Akter, Jesmin (Northern International Medical College Journal, 2016)
Background: Diabetes mellitus (DM) is one of the major public health concerns throughout the world. In 2013, there were 382 million people living with DM, and this number is projected to increase to 471 million by 2035. It affects large number of people of wide range of ethnic and economic levels in both developed and developing countries. Objective : The study was undertaken to assess the knowledge regarding diabetes mellitus among rural people in a selected area of Bangladesh. Methods : A descriptive type of cross sectional study was conducted from November 2015 to January 2016 among 400 people of a village of Gazipur district. The data were collected by using pre tested, semi-structured, interviewer administered questionnaire. Non probability purposive sampling technique was followed. Knowledge related variable were initial symptoms, curability, prevention, risk factors, complications, changes occur inside the body, perceived causes and investigation of DM. Data analysis was done by statistical software, SPSS version 20. Results : Out of 400 respondents, majority (47.50%) were in the age group of 21-30 years. Most (58.25%) of them were male and in terms of educational status 80.5% respondents were literate having varying levels of education. Majority (48.75%) of respondents were service holder. Nearly all of respondents (92%) heard about DM and their source of information was from neighbour 28.89% followed by health care provider 27.71%. Majority of respondents had good knowledge regarding initial symptoms 53.80% and curability 60.86% of DM. Most of them had fair knowledge regarding prevention 35.86% and risk factors 48.09% of DM. Majority 70.92% respondents had poor knowledge regarding complications of diabetes mellitus. Most respondents had no knowledge regarding changes occur inside the body 75.27%, perceived causes of DM 61.69% and investigation 61.41% of DM. Conclusion : This study concluded that good knowledge was found on initial symptom and curability of Diabetes mellitus, fair knowledge on risk factor and prevention and poor knowledge was found regarding complications of DM. No knowledge was found regarding changes occur inside the body, perceived causes and investigation of Diabetes mellitus. Therefore, effective awareness and health education program to the rural people regarding various aspects of Diabetes mellitus are in urgent need. Northern International Medical College Journal Vol.7(2) Jan 2016: 131-134